Caminhos e descaminhos dos municípios produtores de petróleo: o papel dos royalties no desempenho das finanças públicas municipais no estado do Rio Grande do Norte - Silva, Maria Janaina Alves da (2007)
It analyzes the magnitude, the nature and the direction of public revenues and the public expenses in oil and natural gas producing municipalities in the state of Rio Grande do Norte in the post-constituent period, and, more precisely, from the approval of Law 9.478/97, called Oil Law . It argues the fiscal federalism normative theory, the typology and the role of the intergovernamental transferences in the performance of the public finances of the local governments. Shows that the economy of Rio Grande do Norte went through deep social-economic changes in the last few decades, among which includes the discovery of the oil and the natural gas and its importance for the growth of the industrial and services sectors. It points out that the increase of the production and the international price of the oil contributed for the growth in revenues of royalties and the special participation in the beneficiary cities, what did not mean an automatic increase in the resources destined to the investment and in the quality on the provision of the goods and services come back toward the local development. On the contrary, the main conclusion of the work is that the trajectory of the oil producing municipalities is marked by paths and embezzlements in the performance of the public finances and in the provision of public goods and services. Paths, that lead to the improvement of the performance of the public finances and the quality of the public goods and services. Embezzlements, that lead to the inefficiency in the provision of goods and services and the capture of the public resources. That is, the fiscal decentralization is a necessary condition, however not enough to improve the amount and the quality of the public goods and services given by these municipalities. For that it is necessary to advance in the fiscal federalism normative theories, in search of optimum model of federalism in local governments where still predominated by patrimonialism, clientelism, fiscal illusion and the capture of the public resources in benefit of the private interests